Recurrent miscarriage: Are three miscarriages one too many? Analysis of a Scottish population-based database of 151,021 pregnancies. - Bhattacharya, S; Townend, J; Bhattacharya, S (2010)
OBJECTIVE: To assess the risk of further miscarriage or preterm delivery in women with a history of miscarriages in previous pregnancies, adjusting for maternal age and smoking. STUDY DESIGN: Retrospective cohort study using all women with first pregnancies recorded between 1950 and 2000 in the Aberdeen Maternity and Neonatal Databank.Exposure was one or more spontaneous miscarriages, while outcomes assessed were further miscarriage or preterm delivery. RESULTS: There were 143,595 pregnancies with none, 6,577 with one, 700 with two, 115 with three and 24 with four consecutive previous miscarriages. The odds of miscarriage were greater in pregnancies following one previous miscarriage than none {adj.O.R. 1.94 (95% C.I. 1.80, 2.09)}. The risk of miscarriage following two miscarriages was greater than in pregnancies following one {adj.O.R. 1.56 (95% C.I. 1.28, 1.90)}. However, there was no further significant increase in odds of miscarriage for pregnancies following three {adj.O.R. 1.37 (95% C.I. 0.86, 2.17)} previous consecutive miscarriages. Odds of spontaneous preterm delivery were greater following one miscarriage than none {adj.O.R. 1.52 (95% C.I. 1.36, 1.69)} but no further increases in risk were seen. CONCLUSION: After adjusting for age and smoking, the risk of a further miscarriage increased sequentially in women who had one and two miscarriages. Three miscarriages did not increase the odds any further. One miscarriage was associated with an increased chance of spontaneous preterm delivery, but two or three miscarriages did not increase the odds any further.